MENCIPTAKAN RUANG BELAJAR YANG KREATIF DAN NYAMAN BAGI ANAK USIA DINI DI KAMPUNG NAENA MUKTIPURA - Antje Tuasela; Rosdiana; Rani limbong Boli; Shandy Eka Prastya; May Priska Manurung; Rismayanti Sudirman (JOURNAL OF COMMUNITY DEDICATION, 2026)
This Community Service Program (PKM) aimed to create a more creative and comfortable learning environment for early childhood students at TK Negeri 3 Naena Muktipura Village. The background of this program was the limited classroom decoration and visual learning media, which reduced children’s learning motivation and creativity. A participatory and collaborative approach was applied by involving university students, teachers, parents, and children in classroom decoration activities and educational games. The program was conducted in one day through several stages, including needs analysis, preparation, implementation, and evaluation. The results showed a significant improvement in the classroom atmosphere, which became more colorful, attractive, and child-friendly. The children were more enthusiastic and motivated to learn, and they felt proud because their artworks were displayed in the classroom. Teachers and parents also gave positive feedback since the new decorations could be used as learning media. In conclusion, this PKM activity not only improved the physical learning environment but also had a positive impact on the psychological and social aspects of early childhood learning.